Restorative Justice And Legal Reform In Tax Crime Prosecutions: Enhancing Accountability And Efficiency In Indonesia’s Tax System - Laranono, Anton; Santoso, M. Iman; Budianto, Agus; Hartanto, Hartanto (Pelopor Publikasi Akademika, 2025)
This study examines the enforcement of tax crime cases in Indonesia, with a particular focus on the termination of tax crime prosecutions and the perspectives of key stakeholders, including the Indonesian Employers Association (APINDO), the Directorate General of Taxes (DJP), the Financial Audit Agency (BPK), and tax consultants. Using in-depth interviews with selected informants, the research identifies major challenges in tax law enforcement, especially in relation to corporate tax crimes. The findings show that tax crimes frequently stem from collusion between taxpayers and tax officials to evade taxes, coupled with weak corporate governance. The study argues that sanctions for tax crimes should be directed more toward individuals who manage corporations rather than the corporations themselves. Furthermore, the research highlights the rising number of tax crime cases being forwarded for prosecution and notes persistent issues concerning the lack of corporate accountability, including among state-owned enterprises (BUMN). The study also examines the existing legal framework and identifies inconsistencies between administrative and criminal law enforcement in tax matters. These inconsistencies demonstrate the need for clearer legal guidelines and improved coordination among tax authorities, auditors, and law enforcement institutions. The study also underscores the potential role of restorative justice—particularly through tax repayment and fines—as an alternative mechanism to improve taxpayer compliance and increase efficiency in resolving tax disputes. In conclusion, the research offers recommendations for legal reforms, stronger inter-agency coordination, and the enhancement of human resource capacities within tax authorities to ensure that tax crime cases are resolved more effectively and fairly, ultimately supporting Indonesia’s broader fiscal objectives.